Clear cell carcinoma arising from abdominal wall endometriosis: a unique case with bladder and lymph node metastasis - Liu, Haiyuan (BioMed Central, 2014)
The malignant transformation of abdominal wall endometriosis is a rare event and poorly understood. Less than 30 cases have been reported in the literature. Most of the reported cases have a solitary tumor in the abdominal scar. A few cases have metastasis. Here we report a case of clear cell carcinoma in abdominal wall endometriosis with bladder and lymph system metastasis. The patient had a history of abdominal wall endometriosis and recently developed symptoms of urgent urination and inguinal mass. Physical examination and a computed tomography (CT) scan detected lymph node metastasis. CT and cystoscopy confirmed bladder involvement. The patient underwent extensive surgery and chemotherapy. Pathological analysis made a diagnosis of clear cell carcinoma with bladder and lymph node metastasis. The patient was followed up and died of the disease. Symptoms of bladder invasion and lymph node spread could be a sign of malignant transformation. Local invasion and lymph node spread are two important forms of tumor metastasis. Extensive lymph nodes metastasis might be related with poor prognosis.